Antecedents of Online Patient Experience of the Hospital Telemedicine Application and Its Consequences - Cynthia; Ferdi Antonio; Dewi Wuisan (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Hospitals had to adjust by offering telemedicine services in response to the COVID-19 outbreak. In contrast to telemedicine, which is developed independently, telemedicine used to have adequate resources. Unfortunately, few studies have been conducted to capture online patient experience from hospital telemedicine services. Therefore, this study attempts to analyze factors that can affect Online Patient Experience (OPX) and assess the impact on Continue Usage Intention (CUI) and Intention to Recommend (ITR). The independent variables that become the antecedents of OPX are Professional Knowledge (PKL), Physician Rank (PRK), Physician Image (PIM), Response Speed (RSP), Service Commitment (SCM), Service Attitude (SAT), and Communication Efforts (CEF). This study is a quantitative survey with cross-sectional data obtained by questionnaire instrument. Respondents were taken purposively using judgment sampling to get those who had received telemedicine services managed by a large group of hospitals in Jakarta. Based on the result, 172 respondents were eligible. The result indicated that all the antecedents studied had a positive and significant relation (p-value < 0,05) with OPX. The results also found that RSP (β = 0.317), SCM (β = 0.216), and PIM (β = 0,186) are the three constructs that play the dominant role. Thus, it is important to create a positive online patient experience so that patients can continue to use teleconsultation services and recommend them to others.